KESABARAN DAN KESEHATAN MENTAL DALAM BIMBINGAN KONSELING ISLAM - Najamuddin, Najamuddin (Tasamuh: Jurnal Studi Islam, 2018)
Every human must be able to balance between intellectual intelligence and emotional intelligence. Emotional intelligence is measured of the ability to control the emotion and to refrain. In Islam, the ability of controlling the emotion and patience are mentioned the patience. Patience demands patience in the face of something difficult, heavy, and bitter, to be accepted and faced with full responsibility. Nowadays, patience is understood by many people to aim toward passive nature of patience, in meaning of resigning does not do anything when faced with problems. While in Islamic view, patience means to be strong, to stand firm, or not to despair when facing obstacles, and to keep trying maximally. In addition, someoneâs mental health is the ability to adjust to the circumstances encountered, can utilize all the potential and talent as much as possible and bring to the harmony in life must also be considered. Meanwhile, Islamic counseling is a process of providing assistance to individuals to realize again its existence as a creature of God who should live in harmony with the provisions and instructions of God so as to achieve happiness in the world and in the afterlife. Urgency of preaching with the concept of patience that preaching can help clarify and illuminate the madu about how patience is consistent with the Quran and hadist. The existing of preaching is so that the mistake in understanding the patience can be reduced. The problematic society today is not only aboutÂ material issues, but also about psychological problems. So, between patience, mental health and counseling Islam must be framed in preaching.